Effect of Various Avian Egg Yolk Types on the Viability and Longevity of Post-Thawed Resiquimod-Sexed Spermatozoa in Sapera Goats - Setiadi, Deffany Wulandari; Solihati, Nurcholidah; Darodjah, Siti (Faculty of Animal Husbandry, Universitas Padjadjaran, 2026)
Improving the reproductive efficiency of Sapera goats through artificial insemination necessitates optimal quality of sexed frozen semen. This study aimed to determine the effect of various avian egg yolk types on the viability and longevity of post-thawed Sapera Goat spermatozoa sexed using the Resiquimod-based swim-up method. The research used a Completely Randomized Design (CRD) with four egg yolk types: Commercial Chicken (T1), Native Chicken (T2), Quail (T3), and Duck (T4) as treatments and five replications. Data were analyzed using One-Way ANOVA and Duncan’s Multiple Range Test. The results indicated that post-thaw viability ranged from 53.30–64.90% in the upper layer, while longevity ranged from 26.17–29.46 hours in the upper layer and 25.11–28.95 hours in the lower layer, showed no significant differences among treatments. Conversely, the egg yolk type significantly influenced viability in the lower layer (P < 0.05). Specifically, Native Chicken (T2), Duck (T4), and Commercial Chicken (T1) egg yolks maintained superior and stable viability (60.90%, 59.80%, and 56.20%), whereas Quail egg yolk (T3) exhibited significantly lower performance (52.40%). These findings suggest that the choice of egg yolk is critical for maintaining the sperm viability of the lower layer in Resiquimod-based sexed semen.